Modelling and analysis of real world airport gate allocation problem - Neuman, Urszula Monika (2015)
With airports becoming busier and often struggling with insufficient capacity, the efficiency of the airports resource utilisation becomes more and more important all over the world. The efficiency may be improved by integration of the airport operations which historically were handled in separation. More effective resource utilisation would not only smooth the airport operation but also should have a positive environmental impact. The gate allocation problem is one of the important airport operations, which is often solved without considering the links with other airport operations. Modelling and analysis of new constraints which allow the ground movement information to be taken into consideration in the allocation planning in advance as well as design of appropriate solution methods are discussed. It is observed that when the additional information from the ground movement is incorporated in the allocation planning process the number of expected routing conflicts, both around gates and on taxiways, drops. This should results in a smoother airport operation during the day of operation. Data from Manchester Airport is used in this thesis to build the model, as well as to test and to validate the solution methods.